Influence of climate-smart technologies on the success of livestock donation programs for smallholder farmers in Rwanda - John M. Kandulu; Alec Zuo; Sarah Wheeler; Theogene Dusingizimana; Mizeck G. G. Chagunda (Mitigation and Adaptation Strategies for Global Change, 2024)
Climate change threatens the livelihoods of Sub-Saharan African farmers through increased droughts. Livestock donation programs offer a potential solution, but their effectiveness under climate stress remains unclear. This study assesses the economic viability of integrating climate-smart technologies (cowsheds and biogas plants) into these programs in Rwanda. Using a stochastic benefit–cost analysis from the beneficiary perspective, we evaluate the net gains for households receiving heifers compared to the current program. Our findings reveal that integrating climate-smart technologies significantly enhances economic viability. Households with cows and climate-smart technologies can possibly realise net benefits 3.5 times higher than the current program, with benefit–cost ratios reaching 5:1. Beyond economic benefits, adopting biogas reduces deforestation, greenhouse gas emissions, and respiratory illness risks. This study demonstrates that integrating climate-smart technologies into livestock donation programs can generate positive economic, environmental, and health benefits, leading to more resilient and sustainable smallholder systems. However, overcoming implementation challenges requires tailored policy packages addressing local barriers.
Keywords: 330; Aid effectiveness; Sustainable economic development; Low- and medium-income countries; Poverty reduction